Utilization of the Sisfor-Bidanku Application for Early Detection of Child Development: Sisfor-Bidanku for Early Detection - Suriana (Innovative Approaches in Health Science Journal, 2025)
Background: The World Health Organization reports that 5–25% of preschool children experience minor brain dysfunction, including impaired fine motor development. Achieving the 2030 Sustainable Development Goals (SDGs) emphasizes “nurturing care” to support early childhood development, as developmental deviations remain a leading cause of morbidity. Objective: This study aimed to evaluate the effectiveness of the Sisfor-Bidanku application in the early detection of child development. Method: A pretest–posttest design was conducted at Integrated Health Service Posts (Posyandu) in the Campalagian Polewali Mandar Community Health Center area during August–September 2019. Using purposive sampling, 20 midwives were recruited and trained to apply the Sisfor-Bidanku application in child development screening. Data were collected using questionnaires comparing the ease of use between the application and conventional media. Statistical analysis was performed with the Mann–Whitney test. Results: Twelve midwives (60%) reported that the Sisfor-Bidanku application was easier to use compared to only five midwives (25%) using conventional methods. However, the Mann–Whitney test showed no significant difference between the two media (p = 0.080). Conclusion: Although no statistically significant difference was found, more midwives perceived the Sisfor-Bidanku application as easier to use, suggesting its potential as a supportive tool for early detection of child development.